THE PSEUDO-SLAVIC REALIA IN PSEUDO-ETHNIC FANTASY: THE ISSUES OF TRANSLATION INTO THE RUSSIAN LANGUAGE - Nadezhda V. Rabkina (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
To date, the traditional fantasy genre that has its roots in European folklore is transforming as authors seek new, fresh mythological foundations and exotic forms of narration. In an attempt to conquer foreign markets, some of them deploy Slavic mythology and embed words of Slavic origin to create their magical worlds. However, the resulting product is often a Pan-Slavic fantasy universe that refers to no specific culture. In this research, ‘pseudo-ethnics’ denotes an exotic atmosphere created by words associated with a broad linguacultural cluster. The object of the study was the vocabulary used to denote pseudo-Slavic realities in the novel Shadow and Bone by Leigh Bardugo and its film adaptation, as well as the translation techniques employed by the Russian translators. Leigh Bardugo used pseudo-Russian anthroponyms, toponyms and words that denote everyday objects and magical creatures. They represent Latinized Russian borrowings and seemingly authentic neologisms that deploy some morphological and phonetic language features an English-speaking reader might associate with the Slavic culture. However, when translated for an audience with a Slavic ethnic background, the pseudo-ethnic fantasy book or film loses its exotic flavor. The translation techniques for Latinized Russian words conveying the pseudo-ethnic atmosphere are de-transliteration and de-transcription. As part of the translation, translators had to adhere to the grammar rules of the Russian language and eliminate grammatical errors in parts of speech or gender.